?PREPARATION OF HYDROGELS BASED ON PYA-ACRYLIC ACID USING N,N-METHYLENEBISACRYLAMIDE As CROSSLINKING AGENT - Khan, A Rasheed; Farooqui, Z H; Hasan, Shabih-ul-; Imran, Asif (Biological Sciences - PJSIR, 2000)
A transparent hydrogel based on PYA-acrylic acid using N,N-methylenebisacrylamide as crosslinking agent was prepared. Effects of deionised water, distilled water, tap water, aqueous solution of NaCl and NaOH were examined. Degree of swelling was maximum in deionized water, in aqueous NaCl it became minimum whereas it increased in alkaline medium. Increment in degree of swelling was due to the formation of carboxyl anions (-COO·) in the polymer network leading to the development of strong electrostatic forces. Dry hydrogel was white polymeric material.insoluble in most ofthe organic solvents. Decomposition started after 170°C. The refractive index of hydrogel was 1.332-1.345.